Floer potentials, cluster algebras and quiver representations - Albers, Peter; Bertozzi, Maria; Reineke, Markus (Mathematische Zeitschrift, 2025)
We use cluster algebras to interpret Floer potentials of monotone Lagrangian tori in toric del Pezzo surfaces as cluster characters of quiver representations (see Theorem 4.3 for the precise statement).
Gesehen am 26.11.2025